(untitled) (Journal of the College of Basic Education, 2022)
This paper aims to build a low-cost, t reliable, weather monitoring system capable of acquiring and recording data. The proposed system has three sensors that measure the temperature, wind speed and wind direction, respectively. The analogue outputs of the sensors will be transmitted through the air and received by the weather system to be converted to digital signals and further processed by a microcontroller, acting as data logger. The logged data can then be transferred to a PC having a graphical user interface program for further analysis or printing the .measurementsThe system has many advantages like it is a small size and have huge memory capacities, have on device LCD display, lower cost if compared with other climate monitoring system and have high processing speed, high precision and greater portability.